2022
DOI: 10.1002/ana.26496
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Neural Correlates of Emotional Behavior during Prefrontal Seizures

Abstract: This study was undertaken to characterize clinical expression and intracerebral electroencephalographic (EEG) correlates of emotional expression during prefrontal epileptic seizures. Methods: We performed a descriptive analysis of seizure semiology in patients explored with stereo-EEG (SEEG) for pharmacoresistant prefrontal epilepsy, using a semiquantitative score for seizure-related emotional behavior. Two independent observers scored occurrence and intensity of objective emotional features (face/body movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
0
8
1
Order By: Relevance
“…While our research mainly focused on subjective emotional experiences. The difference between Singh et al 15 and our study probably due to subjective experience of fear and the objective behavioral function were controlled by different brain networks.…”
Section: Fearcontrasting
confidence: 86%
See 4 more Smart Citations
“…While our research mainly focused on subjective emotional experiences. The difference between Singh et al 15 and our study probably due to subjective experience of fear and the objective behavioral function were controlled by different brain networks.…”
Section: Fearcontrasting
confidence: 86%
“…A recent study about emotional behavior during prefrontal seizures of Singh et al 15 found that positive behavioral during seizures had predominant involvement of the frontopolar and anterior orbitofrontal regions. However, our research mainly focused on subjective emotional experiences in relative normal brain regions, so our conclusions were slightly different from the study of Singh et al 15 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations